Prognostic value of choroidal vascular index in determining response to intravitreal dexamethasone implant treatment used in refractory diabetic macular edema - İlgüy, Serdar; Işık, Mehmed Uğur (Springer Science and Business Media LLC, 2023)
To investigate the effect of intravitreal dexamethasone (IVD) implant injection, which was used in the treatment of DME, on CVI and to investigate whether CVI can be used as a prognostic marker in the treatment of anti-VEGF resistant DME. A retrospective observational and comparative study. Twenty-five eyes of 25 patients with refractory diabetic macular edema who underwent intravitreal dexamethasone (IVD) implant and 50 eyes of 50 healthy patients were included in the study. Central macular thickness (CMT), subfoveal choroidal thickness (SFCT), luminal choroidal area (LCA), total choroidal area (TCA), stromal choroidal area (SCA), and choroidal vascularity index (CVI) were measured on optical coherence tomography. There was no significant difference between the groups in terms of age and gender. When the pre-treatment values in the IVD group were compared with the healthy group, LCA and SCA values were higher, and CVI ratios were lower in the IVD group compared to the control group. When baseline, 1st, and 3rd months after injection were compared, it was determined that there was a significant decrease in CMT and LCA. There was no statistically significant difference in SFCT, TCA, and CVI. There was a significant negative correlation between baseline CVI and 3rd month CMT after IVD (rho: - 0.643, p: 0.001). It was observed that the baseline and 1st month LCA values were significantly higher than the 3rd month. The choroidal vascular structure may be affected by IVD treatment. CVI may also have value as a prognostic marker in monitoring the response to treatment.
Keywords: Diabetic Retinopathy; Choroid; Diabetes Mellitus; Humans; Prognosis; Macular Edema; Dexamethasone; Tomography, Optical Coherence; Retrospective Studies; 3. Good health